Investigation and evaluation of the efficiency of palm kernel oil extract for corrosion inhibition of brass artifacts - Mohamed M. Megahed; Eman AbdElRhiem; Wesam Atta; Nabil Abdel Ghany; Mohamed Abdelbar (Scientific Reports)
Abstract Brass (Cu–Zn alloy) used in the crescent of the Al-Maradani Mosque pulpit is subjected to corrosion under certain conditions, such as exposure to polluted air, oxidizing acids, and compounds containing sulphur or ammonia. This study aimed to evaluate the effectiveness of palm kernel oil extract (PKO) as a green corrosion inhibitor for protecting brass artifacts. The crescent was analyzed using metallographic microscopy, scanning electron microscopy (SEM) with energy-dispersive X-ray (EDX), and X-ray diffraction (XRD) to identify its alloy composition, microstructure and corrosion products. The analyses confirmed the crescent was made of a brass alloy (Cu–Zn) and formed by hammering, with corrosion layers composed primarily of cuprite and clinoatacamite, covered by dust containing calcite and quartz. The corrosion protection efficiency of the PKO was evaluated using brass coupons, simulating the artifact of the alloy. Electrochemical methods, including the open circuit potential (OCP), Tafel, and electrochemical impedance spectroscopy (EIS), were used to assess the performance of palm kernel oil on brass coupons at different concentrations (1, 3, 5, 7%). Electrochemical tests showed that corrosion inhibition efficiency increased with higher palm kernel oil concentrations, with the 7% concentration exhibiting the highest corrosion protection, up to 99.7%.